Bilateral Pars Plana Vitrectomy for Vitreous Opacities and Epiretinal Membrane in Gaucher Disease. (July 2018) - Storey, Philip P.; Tan, Jeffrey J.; Rayess, Nadim; Rao, Narsing
Purpose: To describe the clinical course of a patient with Gaucher disease, a rare lipid storage disorder, who presented with bilateral visually striking vitreous opacities and epiretinal membranes. Methods: Case report. Results: Pars plana vitrectomy and membrane peel were sequentially performed in both eyes with successful resolution of the opacities and macular puckers, although in one eye, the internal limiting membrane was not initially peeled, and a second surgery was required when the epiretinal membrane rapidly returned. Eight months after surgery, visual acuity improved from 20/150 bilaterally to 20/40 and 20/50 without recurrence of vitreous opacities. Conclusions: Pars plana vitrectomy with membrane peel for patients with vitreous opacities and epiretinal membranes in the setting of Gaucher disease can be an effective treatment option.